BIMBINGAN DAN PENYULUHAN PENGGUNAAN SOSIAL MEDIA (INSTAGRAM) SEBAGAI SARANA MEMPROMOSIKAN OLAHAN HASIL PERTANIAN WARGA DESA/KELURAHAN TLEKUNG KECAMATAN JUNREJO KOTA BATU - Ellyn Eka Wahyu; Halid Hasan; Heru Utomo; Pudji Herijanto; Mahmudatul Himma (Publisher UPT P2M Politeknik Negeri Malang, 2018)
Tlekung Village is the one of village that was located in Junrejo, Batu. There are several potentialproductincludes Dairy products, Rice and Vegetables such as: Mushrooms, Carrots,Mustard, Sweet Potatoes and also Sweet Corn. In general, all of the products were sold in the local market. But actually, the amount of agricultural productare higher than the amount ofproducts that absorbed by the market. This phenomena bring special attention from the womens of Tlekung Village by taking the initiative to process the agricultural products into cakes such as Bolu Cake, Pastry and or Ice Cream. Furthermore, there were some obstacles that faced by the womens of Tlekung Village.They couldn’t promote and sell the cakes through social media because in general the residents of Tlekung Village only knew social media as a media to communicate for each other. From that, We as the PkM Team provided an alternative to solve the problems by guiding and mentoring all of womens at Tlekung Village to promote and sell the cakes using Instagram so that the promotion can be wider and it can covered all of region on this city.All of participants were able to practice the results of the guiding and mentoring process, by promoteand sell cakes such as Kue Bolu, Pastry and or Ice Cream through Instagramto the public, so we hope that this method canincrease the income of the residents of Tlekung Village in the future.